ROLE OF NATURAL TOOTHBRUSHES IN CONTAINING ORAL MICROBIAL FLORA-A REVIEW - Sagar, Sandra (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: To review the interest in the use of natural tooth brushes as environment friendly and cheap tool for dental care and oral hygiene. Methods: The role of natural tooth brushes obtained from Gum Arabic tree, Meswak, Banyan, Neem, Apple, Mangosteen, Licorice, Olive, etc. versus modern tothbrushes in controlling oral microbial flora were reviewed from available literature. Result: Natural toothbrushes reported dental protection similar to modern toothbrushes. They are more ecological in its life-cycle, lower cost (0-16% of the cost of a toothbrush). They require no tooth paste, maintenance and can combat bad breath. Conclusion: Using Natural toothbrushes will be more beneficial to our oral hygiene than modern brushing techniques in controlling oral microbial flora. Keywords: Meswak, Banyan, Microbial flora, Dental caries.